Saberes docentes no ensino superior: perspectivas sobre o ensinar e o aprender no curso de Direito - Galvão, Tailanne Reis Pecorelli (2017)
Teaching is as dynamic as Law, the points of view, as the Law is constantly updating for the purpose of society. That is, just as the law is constituted as a norm of conduct for the conflicts and dissensions that arise in social relations, with security control or control of social dynamics, and its evolution according to social development, as changes in society. In this dissertation present the results of a research on the teaching knowledge in higher education: perspectives on teaching and learning in the Law course. I had as general objective the knowledge mobilized by the teacher in the teaching-learning process of the students. To do so, specifically, to prepare a study, to accompany the students and teachers, the necessary knowledge to practice a law course, examine the teachings of teachers in relation established by the student and teacher, and, finally, discuss the knowledge of the Teaching practice, Significant for a learning of the students. (2002), Gauthier (2006), Freire (1996 and 2000) and Pimenta (1998, 2002), Shulman knowledge (1987) and Masetto competences (2002) (Activity was structured from theoretical knowledge about knowledge De Tardif 1998 and 2003), which are based on teaching practices of students 'and teachers' experiences. For the development of research with a qualitative approach, with the scope of a discourse behind the subjects' failures, which became known through the application of the questionnaire and the effective participation of the subjects in the research by a fundamental interview in 8 (eight) practical cases, constructed from the reality of some students and professors of the law course of institutions of the city of Feira de Santana- Ba. The research was carried out with 1 (one) professor and 4 (four) students of the Law course of the State University of Feira de Santana - UEFS. Analysis of interviews using Bardin's content analysis techniques (2010), for qualities found 3 (three) categories that represent the knowledge necessary to teach law course, which influence the students' learning, which correspond to the practice of UEFS teachers : Content appropriation, teacher-student relationship and pedagogical practice. The results indicate the basic need for a specific training for teachers who carry out their teaching activities in Law courses. It was noted that both the students and the teacher reveal the importance of the teaching knowledge to the students' learning.